Number 20 (August 1989) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 1989)
(August 1989) - Distribution and Conservation Status of the Northern Studfish, Fundulus catenatus, in Indiana. By J.E. Thomerson and L.N. Smith, 6pp. New Records and Comments on the Distribution of Blair's Starhead Topminnow, Fundulus blairae (Fundulidae). By M.G. Warren and P.E. Denette, 3 pp. The Chestnut Lamprey, Ichthyomyzon castaneus Girard, in the Mobile Basin. By R.L. Mayden, et al., 3 pp. Diet of Juvenile Bowfm, Amia calva Linnaeus, in the Sipsey River, Alabama. By K.S. Frazer et al., 3 pp.
Keywords: fishes; fundulus catenatus; indiana; blair& #x27; s starhead topminnow; fundulus blairae; fundulidae; chestnut lampree; ichthyomyzon castaneus girard; mobile basin; juvenile bowfm; amia calva linnaeus; sipsey river; alabama